أثر المناخ على الإصابة بمرض ذات الرئة في قضاءي الفاو والقرنة - Hussein Naji, Khayria; Abdulwahab Hasan Al-Asadi, Prof. Dr. Kadhim (Basra studies journal, 2023)
The research deals with the study of pneumonia in Fao and Qurna districts for the duration (2009/ 2010-2019 / 2020). The study included (research problem, research hypothesis, research objectives, research methodology, research boundaries) and analysis of the monthly change of pneumonia and the statistical relationship between elements, climatic phenomena and pneumonia using simple association coefficient (Pearson). The study relied in the process of analysis on analytical and quantitative approaches.